Cele strategiczne i operacyjne hoteli a jakość usług - Jaremen, Daria Elżbieta (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
Services quality improvement in hotel industry requires the formation of a specific bunch of objectives that the hotels aim at implementing. Such bunches of objectives put forward by Polish hotels become the centre of interest of the hereby article. The study takes up an attempt to identify and evaluate them from the point of view of their focusing on services level improvement. Conclusions were based on the research of selected hotels situated in the Karkonosze and Izery Mountains. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Gospodarka a Środowisko (6); 2006; nr 1145, s. 111-119